Adsorptive Removal of Alizarin Red S onto Sulfuric Acid-Modified Avocado Seeds: Kinetics, Equilibrium, and Thermodynamic Studies - G. Bharath Balji; P. Senthil Kumar (Adsorption Science & Technology)
The present work evaluates the synthesis of a novel, inexpensive, and environmentally friendly chemically-treated avocado seed powder (CTASP) as an adsorbent in removing alizarin red S (ARS) from synthetic solution. By using a set of analytical techniques, including FTIR, XRD, EDX, RS, and SEM, the adsorbent was characterized for its physical and chemical properties. Batch study experiments were conducted to determine the effectiveness of the CTASP as an adsorbent. The maximum adsorption capacity of 67.08 mgg-1 was attained at optimum conditions of 3 gL-1 adsorbent dosage, pH 3, contact time of 30 min, and at temperature 303 K. After 30 minutes, the equilibrium was reached, and the experimental data was explained for isotherm, kinetic, and thermodynamic processes. The results indicated that pseudo-second-order kinetics and the Freundlich isotherm were the best fits for the data. The findings of the analysis of the thermodynamic parameters for the process showed that the system was an exothermic and spontaneous. According to the desorption studies, 0.1 M NaOH can be utilized as a separating reagent to desorb 90.53% of ARS that was adsorbed. Regeneration experiments were conducted to make the process more practical and affordable, and it was discovered that the CTASP adsorbent could be successfully regenerated up to four times. In comparison with other adsorbents, the current low-cost adsorbent had the exceptional regenerative capability and delivered multilayer adsorption capacity. Additionally, it has been demonstrated that the CTASP is an effective material for the detoxification of ARS dye from wastewater.